Why do investors choose a mutual fund? - Fendy Cuandra; Jackson Rinaldo (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2021)
The purpose of this research is to identify the factors that support mutual funds investment decisions through overconfidence, risk perception, loss aversion, availability, and herding variables on the investment decisions of the residents of Batam City. Data were collected through questionnaires and processed using multiple linear regression. The results of testing and processing research data show that overconfidence, loss aversion, and herding significantly positively affect investment decisions, while risk perception and availability do not affect investment decisions.